Successful endotracheal intubation guided by tracheal ultrasonography in a critical patient with a difficult airway - Behnan Gulunay (Turkish Journal of Emergency Medicine)
In critical care, effective airway management, especially during cardiopulmonary resuscitation (CPR), is vital. Endotracheal intubation, although common, poses challenges in patients with difficult airways. Traditional methods for confirming tube placement, particularly during CPR, can be unreliable. Tracheal ultrasonography is emerging as a valuable tool for guiding intubation and confirming tube placement in real time. A case of a 72-year-old with respiratory distress, chronic obstructive pulmonary disease, and heart failure is described. Despite initial treatment, emergency intubation was necessary, but the initial attempt failed due to a difficult airway. Tracheal ultrasonography guided the intubation process and confirmed tube placement in real time, leading to successful intubation and improved outcomes. This technique shows promise in optimizing airway management during CPR, offering real-time visualization, and minimizing complications. This case underscores the potential of ultrasound-guided techniques in emergency airway management. Further research is needed to fully understand their benefits and limitations in such settings.